PENGARUH FASILITAS KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN: (Studi Pada PT Karunia Berlian Makmur) - Abu Bakar Sidik, Haris; Aziz, Syaefudin; Taolin, Maximus L (Yayasan Pendidikan Cahaya Budaya Indonesia, 2022)
This study aims to determine the simultaneous influence of work facilities and work environment on employee performance and the partial influence of work facilities and work environment on employee performance at Karunia Berlian Makmur PT. This research is a quantitative research with a descriptive approach. The population in this study were all employees PT.Karunia Berlian Makmur totaled 250 employees with a sample taken of 154 respondents. The method of analysis in this study uses multiple linear regression analysis with the help of SPSS version 21 software. The results of this study indicate that the work facilities and work environment simultaneously affect employee performance with the value f count > f tabel (438,548 > 3,055), and the significance value is 0,000 < 0,05, t test results approved that work facilities and work environment having a positive and significant effect towards employee performance with the value of t count > t tabel, with each score 2,230 and 6,612 with a significance value of work facilities > 0,05 and work environment < 0,05. The multiple linear regression model in this study is Y = 12,238 + 0,209X1+0,632X2.